Potential Role of the Retrotrapezoid Nucleus in Mediating Cardio-Respiratory Dysfunction in Heart Failure With Preserved Ejection Fraction - Toledo, Camilo; Ortolani, Domiziana; Ortiz, Fernando C.; Marcus, Noah J.; Del Rio, Rodrigo (Frontiers in Physiology, 2022)
A strong association between chemoreflex hypersensitivity, disordered breathing, and elevated sympathetic activity has been shown in experimental and human heart failure (HF). The contribution of chemoreflex hypersensitivity in HF pathophysiology is incompletely understood. There is ample evidence that increased peripheral chemoreflex drive in HF with reduced ejection fraction (HFrEF; EF<40%) leads to pathophysiological changes in autonomic and cardio-respiratory control, but less is known about the neural mechanisms mediating cardio-respiratory disturbances in HF with preserved EF (HFpEF; EF>50%). Importantly, it has been shown that activation of the central chemoreflex worsens autonomic dysfunction in experimental HFpEF, an effect mediated in part by the activation of C1 catecholaminergic neurons neighboring the retrotrapezoid nucleus (RTN), an important region for central chemoreflex control of respiratory and autonomic function. Accordingly, the main purpose of this brief review is to discuss the possible role played by activation of central chemoreflex pathways on autonomic function and its potential role in precipitating disordered breathing in HFpEF. Improving understanding of the contribution of the central chemoreflex to the pathophysiology of HFpEF may help in development of novel interventions intended to improve cardio-respiratory outcomes in HFpEF.